Comparative Study of Landsat and Aster Data by Morphometric Analysis - Kumar, Sujit; Bhandary, Tapasi (Salehan Institute of Higher Education, 2015)
In this paper, a case-study is presented to differentiate between Landsat and Aster data by morphometric analysis. For this the Aster and Landsat digital elevation model (DEM) data of the same study area was taken and then both the data was delineated for the same (common) outlet. The major differences found in between Landsat and Aster data after delineation are in the number of first order stream, axial length of streams, average width and size of watershed. The case study presented will be useful in demonstrating the fact that Landsat DEM has better accuracy than Aster DEM for land cover areas when the DEM data characteristic are kept similar.